If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + -7 + 4w = 8 Reorder the terms: -7 + 2w + 4w = 8 Combine like terms: 2w + 4w = 6w -7 + 6w = 8 Solving -7 + 6w = 8 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 6w = 8 + 7 Combine like terms: -7 + 7 = 0 0 + 6w = 8 + 7 6w = 8 + 7 Combine like terms: 8 + 7 = 15 6w = 15 Divide each side by '6'. w = 2.5 Simplifying w = 2.5
| 46y^2+38y+7=0 | | 3+X+5=X+9 | | 4y+5y-6=y+7+2y-8 | | y=6x^3-18 | | 2x^10+275x^5+243=0 | | -7+15=2x-3 | | x+0.17x=1000000 | | 7+s=8s-(-9) | | 8c-20=21c-7 | | 2+8m=(-17)+3m | | (x^2-9)(2+1)=0 | | 4u^2+4u-v^2-4v=12 | | 15a+16a-3b-12b= | | 3x^2+3y^2-2x+y-5=0 | | x^4+8x^3+26x^2+40x+32=0 | | 5x^2+5y^2+10x-5y+3=0 | | 50x=300-x | | (3r+2s)(4r-3s)= | | 15/2x=2/3 | | (5y^2-2y+1)-(y^2-4y-8)= | | 50+2x=50 | | (5y^2+1)-(y^2-4y-8)= | | 5x^4(3x^2+1x)= | | y^2dx+(xy+3y^3)dy=0 | | 2xy(1+y^2)dx-(1+x^2+x^2y^2)dy=0 | | 3(2x-2)-4(x-6)=4x+8 | | 21((6/7)n) | | 2n^2+3n-560=0 | | 8c^2+2c-3=0 | | 2(9+x)=48 | | 2/d | | 20x+4+4(5x+1)-x+5= |